The Effectiveness of the Explicit and Implicit Grammar Teaching Online to Improve the Grammar Mastery - Haryono, Tan Agung; Fitriati, Sri Wuli; Suwandi, Suwandi (Universitas Negeri Semarang, 2023)
Online classes have become indispensable in the digital age due to the internet's ability to offer invaluable resources and support for second-language classrooms. This practicality has led to widespread adoption across all academic levels, including higher education, resulting in a significant increase in the utilization of online classes. The purpose of the study was to examine how online explicit and implicit grammar teaching improved the degree of comparison mastery of the learners in Structure 2, a grammar course offered by Unika Soegijapranata in Semarang. Explicit grammar teaching involves presenting the rule and then providing examples to illustrate it, as stated by Larsen-Freeman (2014). On the other hand, implicit grammar teaching emphasizes the significance of learning grammatical rules through immersive experiences by providing various phrases and contextual examples (Thornburry, 1999). A quantitative case study was used to carry out the research. The data were collected by the assessment assigned to 19 students in the forms of pre-test and post-test. The students were grouped into 9 participants for the explicit group, and 10 participants for the implicit group. The data were analyzed via Microsoft SPSS version 22. The finding was that both explicit and implicit grammar teaching online had significant effects on the improvement of competencies. Thus, this study emphasizes the importance of considering these methods by lecturers, higher education institutions, and students involved in the learning process.